Al-Qaida in Afghanistan - Stenersen, Anne (Cambridge University Press, 2017)
Since 9/11, al-Qaida has become one of the most infamous and widely discussed terrorist organizations in the world, with affiliates spread across the globe. However, little-known are the group's activities within Afghanistan itself, something which Anne Stenersen examines in this book. Using an array of unique primary sources, she presents an alternative narrative of al-Qaida's goals and strategies prior to 9/11. She argues that al-Qaida's actions were not just an ideological expression of religious fanaticism and violent anti-Americanism, but that they were actually far more practical and organized, with a more revolutionary and Middle Eastern-focused agenda than previously thought. Through Stenersen's analysis, we see how al-Qaida employed a dual strategy: with a small section focused on staging international terrorist attacks, but at the same time a larger part dedicated to building a resilient and cohesive organization that would ultimately serve as a vanguard for future Islamist revolutions.